APLIKASI PENGARUH ABU SEKAM PADI TERHADAP PERTUMBUHAN SEMAI AREN (Arenga pinnata Merr) PADA MEDIUM GAMBUT - Pandu Rasyidi; M. Mardhiansyah Mardhiansyah; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Aren (Arenga pinnata Merr) is a type of palm plant that produces fruit, sap and starch or flour in the stems. Peat from its natural formation process has a low fertility rate because it contains high organic acids. Rice husk ash is the result of burning rice husk which can improve soil properties, so that it can support more optimal plant growth and development. The purpose of this research was to determine the effect of the application and the best composition of rice husk ash on the growth of palm seedlings on peat medium. This study used a non-factorial completely randomized design (CRD), which consisted of one factor, namely the dose of rice husk ash with 5 treatment levels and 4 replications in order to obtain 20 experimental units. The treatment of rice husk ash (T) consists of 5 levels with the following dosages: T0 = without application of rice husk ash (control) 100% peat, T1 = application of rice husk ash 10% polybag + 90% peat, T2 = application of rice husk ash 20 % polybag + 80% peat, T3 = application of rice husk ash 30% polybag + 70% peat, T4 = application of rice husk ash 40% polybag + 60% peat. The application of rice husk ash affects the dry weight of palm (Arenga pinnata Merr) on peat medium. The best application of rice husk ash at a dose of 40% rice husk ash plus 60% peat can increase the growth of increase in diameter 0.29 mm, plant dry weight of 1.92 g, crown ratio root 2.25. Keywords : Arenga pinnata, rice busk, growth.